Evaluation of a Conservative Pharmacist-led U-500R Insulin Management Protocol in the Primary Care Setting - Cyndi Dumont; Leah Fitzgerald; Connie A. Valdez (SAGE Publishing, 2020)
Objective The objective of this quality assurance study is to evaluate the impact of a conservative, pharmacist-led, U-500R insulin management protocol on diabetes control (A1c) and total daily dosage requirements between August 2016 and August 2018. Methods This was a retrospective chart review of adult patients, aged 18 to 79, with type 2 diabetes and managed with insulin, at 2 federally qualified healthcare clinics in Denver, Colorado. To determine if our conservative pharmacist-led U-500R insulin management protocol impacted efficacy and total daily dosage requirements when converting patients from U-100 to U-500R insulin, we compared the most effective dose of U-500R (defined as the total daily dose (TDD) of U-500R insulin at A1c goal or the lowest tolerated A1c) to the baseline A1c and TDD of U-100 insulin at time of conversion. Results Following conversion of U-100 to U-500R insulin, patients required an average of 21 fewer units of insulin with U-500R than U-100 and achieved an average A1c of 7.2% which reflected a reduction of 3.5 points from baseline. Five patients (62.5%) achieved A1c goal per ADA guidelines, and all patients achieved at least a 1.7 point reduction in A1c, with 1 patient achieving a 6.7 point reduction. Two patients (25%) were still in the process of U-500R titration at the time of data collection, and 1 patient (12.5%) did not achieve goal A1c while under pharmacy management at these clinics. Four of the five patients who achieved A1c goal did so with an overall reduction in total daily insulin dose (average of 57.5 units less than original U-100 dose) resulting in an average A1c decrease of 3.6 points.